Impact of turbulence on magnetic alignment in sediments - Philippe, Édouard G. H.; Valet, Jean-Pierre; St-Onge, Guillaume; Egli, Ramon (Frontiers in Earth Science, 2022)
Rapidly deposited layers (RDL) such as turbidites or hyperpycnites are mostly studied for their sedimentological properties, but are carefully avoided in paleomagnetic studies due to the disturbances caused by such sudden and rapid sediment accumulation. Therefore, these layers can also be seen as potential indicators of sediment parameters susceptible of affecting the alignment of magnetic grains and ultimately the acquisition of the natural remanent magnetization (NRM). We have compiled 13 Holocene RDL from core MD99-2222 in the Saguenay Fjord, eastern Canada (St-Onge and al., 2004) with varying thicknesses (from 7.1 cm to 1510 cm) and 4 Quaternary turbidites of different origins, to document the influence of sedimentary and magnetic parameters on NRM acquisition. We found a logarithmic relationship between RDL thickness on the one hand, and the amplitude of inclination changes and magnetic grain sizes on the other. Inclination and grain sizes are themselves correlated to each other by a logarithmic law. As there is no relationship between inclination deviation and depth, compaction alone cannot account for such large effects on inclination. Flocculation is grain size sensitive, but it is expected to affect mainly the NRM intensity, rather than its direction. Turbulence that prevails during the rapid deposition of sediments during such events is most likely the dominant factor.